2016
DOI: 10.1016/j.ypmed.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and predictors of sexual health among adolescent Latinas in the United States: A systematic review of the literature, 2004–2015

Abstract: Adolescent Latinas in the United States (US) are disproportionately affected by early pregnancy, sexually transmitted infections (STIs) and human immunodeficiency virus (HIV) in comparison to their non-Hispanic white counterparts. However, only a few studies have sought to understand the multi-level factors associated with sexual health in adolescent Latinas. Adhering to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, we conducted a systematic literature review to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 56 publications
1
10
0
3
Order By: Relevance
“…According to the literature, our findings confirm that early sexual debuts (Muindia et al, 2014;Santelli et al, 2000) and risk-taking personality profiles (Lee & Hahm, 2010;Morales-Alemán & Scarinci, 2016) are positively associated with sexual behaviours (RQ2). In particular, the use of drugs and alcohol is strongly related to sexual conduct (Bryan et al, 2012;Guo et al, 2002;Khan et al, 2012;Luk et al, 2016;Ritchwood et al, 2016;Tapert et al, 2001).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…According to the literature, our findings confirm that early sexual debuts (Muindia et al, 2014;Santelli et al, 2000) and risk-taking personality profiles (Lee & Hahm, 2010;Morales-Alemán & Scarinci, 2016) are positively associated with sexual behaviours (RQ2). In particular, the use of drugs and alcohol is strongly related to sexual conduct (Bryan et al, 2012;Guo et al, 2002;Khan et al, 2012;Luk et al, 2016;Ritchwood et al, 2016;Tapert et al, 2001).…”
Section: Discussionsupporting
confidence: 85%
“…Research on the sexual behaviours of migrants is generally focused on the topics of sexual risk and health-related consequences (Gordillo, 2010;Hirsch, Wardlow, & Smith, 2009;Minian, 2018). Most research has largely focused on several specific communities (respectively, Latinos and Hispanic in the USA and Asiatics/Africans in specific European countries; see, among others, Coleman-Minahan, 2010; Gras, Weide, Langendam, Coutinho, & van den Hoek, 1999;Minnis & Padian, 2001;Morales-Alemán & Scarinci, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These authors also note the importance and influence of acculturation processes and generation on migrants’ decision-making regarding SRH protective behaviours. A systematic review examining the correlates and predictors of sexual health among adolescent Latinas in the United States [24] discussed cross-generational research. The authors indicated that while some studies attempt to capture the construct of SRH in a multi-dimensional way the concept tends to be reduced to language preference or migrant generation without the exploration of more nuanced understandings.…”
Section: Introductionmentioning
confidence: 99%
“…use and that woman's power in the relationship was associated with lower risk of pregnancy [8]. Attitudes and expectancies with regards to sexual behavior informed by gender norms underlie some of the observed disparities in sexual and reproductive health risk; [4,13] for instance, overall, more equitable relationships are associated with sexual health [14].…”
mentioning
confidence: 99%